SISTEM PENGOLAHAN PENDAFTARAN BEASISWA BAGI MAHASISWA STMIK KHARISMA MAKASSAR BERBASIS WEB DENGAN FRAMEWORK CODEIGNITER - Hanif Suherlan; Junaedy; Hendra Surasa (JTRISTE, 2017)
This research aims to build a computerized system for processing registration data scholarships for students STMIK Kharisma Makassar using CodeIgniter Framework. The system is built by using CodeIgniter Framework and database MySQL. Framework CodeIgniter approach MVC (Model, View, Controller), MVC is an application development method which separates the data logic (models) of presentation logic (View) and the process logic (Controller) so that the application development using Framework Codeigniter can be structured. Based on the research, the author has managed to establish a scholarship application processing system using CodeIgniter Framework on STMIK Kharisma Makassar. This application can help Vice Chairman III in data processing scholarships on STMIK KHARISMA, as well as facilitate students who want to make the scholarship application.